Luas Optimal Kawasan Hutan dari Fungsi Ekonomi Hutan Serbaguna - Wahyu Andayani (Jurnal Ilmu Kehutanan, 2022)
The multi-function forests establishment is an appropriate solution for the paradigm transition in forest management from timber management into ecosystem management. Inclusive economic and environmentally friendly business models become a necessity in forest management to ensure the sustainable functions of forests as life support systems. The multi-business in forestry regulated by Ministerial Decree -PerMen-LHK No.8/ 2021- is in line with the spirit of multi-function forests paradigm to increase forest lands productivity, not only timber but also non-timber forest products and environmental services. Although the government has formulated the multi-function forests development concept and its strategic plan several years ago, the forestry sector's contribution in economic valuation, such as national income (PDB—gross domestic product) and non-tax revenue (PNBP—non-tax state revenue) is relatively low. In this disruption era, this forest management transition becomes a necessity. The multi-function forests establishment could become a realistic management model to implement business diversification and innovation and optimize forestry competitiveness at each business level to accommodate social, economic, and environmental aspects of forest management.